2009
DOI: 10.4049/jimmunol.0804155
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Th2 Cell Differentiation and Allergen-Induced Airway Inflammation in Zfp35-Deficient Mice

Abstract: Studies of human asthma and of animal models of allergic airway inflammation revealed a crucial role for Th2 cells in the pathogenesis of allergic asthma. Kruppel-type zinc finger proteins are the largest family of a regulatory transcription factor for cellular development and function. Zinc finger protein (Zfp) 35 is an 18-zinc finger motif-containing Kruppel-type zinc finger protein, while its function remains largely unknown. The aim of this study was to clarify the role of Zfp35 in the pathogenesis of Th2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…20 Previous studies have shown that Zfp608 reduced Rag expression in thymocytes and impaired T-cell development. Based upon a total percent identity of 43.6% and a total sequence similarity of 57.6%, Zfp609 is the closest relative to Zfp608 (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…20 Previous studies have shown that Zfp608 reduced Rag expression in thymocytes and impaired T-cell development. Based upon a total percent identity of 43.6% and a total sequence similarity of 57.6%, Zfp609 is the closest relative to Zfp608 (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…28 For example, mice experiments have demonstrated that ZNF271 negatively regulate T-helper cell type 2 cell proliferation and control T-helper cell type 2–dependent diseases, such as allergic asthma. 29 …”
Section: Discussionmentioning
confidence: 99%
“…For example, Zfp35 ( ZNF271 ) appears to influence the pathogenesis of airway inflammation and hyperresponsiveness in asthma by controlling Th2 cell generation and Th2cytokine expression. 19 Many zinc finger proteins have been demonstrated to be involved in transcription. 20 ZNF432 has been found to be associated with inflammatory bowel disease, at P= 8.3 × 10 −5 .…”
Section: Discussionmentioning
confidence: 99%